2017
DOI: 10.1371/journal.pone.0175035
|View full text |Cite
|
Sign up to set email alerts
|

The genetic evolution of canine parvovirus – A new perspective

Abstract: To trace the evolution process of CPV-2, all of the VP2 gene sequences of CPV-2 and FPV (from 1978 to 2015) from GenBank were analyzed in this study. Then, several new ideas regarding CPV-2 evolution were presented. First, the VP2 amino acid 555 and 375 positions of CPV-2 were first ruled out as a universal mutation site in CPV-2a and amino acid 101 position of FPV feature I or T instead of only I in existing rule. Second, the recently confusing nomenclature of CPV-2 variants was substituted with a optional no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
118
3
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(144 citation statements)
references
References 39 publications
9
118
3
4
Order By: Relevance
“…With the exception of Guangxi and Gansu, CPV‐2a has been found in the other 14 provinces. CPV‐2a has also been reported as the predominant variant elsewhere in Asia (Zhao et al., ; Zhou, Zeng, Zhang, & Li, ), previously. Before 2010, CPV‐2c, new CPV‐2a and new CPV‐2b had not been reported in China.…”
Section: Discussionmentioning
confidence: 85%
“…With the exception of Guangxi and Gansu, CPV‐2a has been found in the other 14 provinces. CPV‐2a has also been reported as the predominant variant elsewhere in Asia (Zhao et al., ; Zhou, Zeng, Zhang, & Li, ), previously. Before 2010, CPV‐2c, new CPV‐2a and new CPV‐2b had not been reported in China.…”
Section: Discussionmentioning
confidence: 85%
“…Whereas CPV‐2a and CPV‐2b are the prevalent variants circulating in Asia (Yi, Tong, Cheng, Song, & Cheng, ), and more recently, CPV‐2c has been described in the same continent (Chiang, Wu, Chiou, Chang, & Lin, ; Geng et al, ; Nakamura et al, ; Wang et al, ; Zhao et al, ; Zhou, Zeng, Zhang, & Li, ; Zhuang et al, ), showing molecular signatures different from those of other continents. Indeed, the Asian CPV‐2c variant shows specific amino acids in NS1 (60V, 544F, 545V, 630P) and VP2 (5A/G, 267Y, 297A, 324I, 370R) gene sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Canine parvovirus has still been playing a main role in inducing severe and often fatal gastroenteritis in young or non‐immunized dogs. During years, CPV spread and evolution have been well documented in North and South America, Europe and Asia (Miranda & Thompson, ; Zhou, Zeng, Zhang, & Li, ). More recently, data about its spread were also obtained from Australia and Africa (Amrani et al, ; Castanheira et al, ; Chollom et al, ; Dogonyaro et al, ; Figuiredo et al, ; Folitse et al, ; Kapiya et al, ; Touhiri et al, ; Woolford et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As most recent Asian CPVs, the Nigerian strains displayed other three aa substitutions in the VP2 sequence (F267Y, Y324I and Q370R). While change at aa residue 324 is predominant in all three CPV variants in Asia (Geng et al, ; Yi, Tong, Cheng, Song, & Cheng, ; Zhao et al, ; Zhou et al, ), the other changes have been less frequently observed, mainly in China since 2013, and change Q370R has been detected only in CPV‐2c strains (Geng et al, ; Guo et al, ; Mira, Purpari, et al, ; Mira, Purpari, Lorusso, et al, ; Wang et al, ; Zhuang et al, ). These aa substitutions are located in the greatest variable VP2 GH loop, comprised between aa 267 and 498, but while residue 267 is not exposed on the capsid surface (Chiang, Wu, Chiou, Chang, & Lin, ) and may not affect the antigenicity of CPV (Xu et al, ), residues 324 and 370 could have immunological implications or biological relevance.…”
Section: Discussionmentioning
confidence: 99%